DETERMINAN KEMISKINAN DI SUMATERA - Barika Barika; Retno Agustina Ekaputri; Bambang A Hermanto (Jurnal Ekonomi-Qu, 2023)
The purpose of this study is To analyze the effect of economic growth. capital expenditure, education and investment on poverty in Sumatra. This study uses poverty data, economic growth data, government spending data, gross fixed investment ratio data in Sumatra in 2011-2020. Influence testing between variables will be carried out using the panel data regression analysis method. The R2 value of 0.55 which means that the variables of economic growth, education, unemployment and investment are able to explain the variable poverty rate of 55%. The poverty variable is a bound variable that is influenced by economic growth, education, unemployment and investment. From the results of data processing, it was found that all variables had a significant effect on poverty in Sumatra